Self-reported responsiveness to direct-to-consumer drug advertising and medication use: results of a national survey - Somes Grant W; Kukkamma Lisa; Dieringer Nicholas J; Shorr Ronald I (BMC, 2011)
Abstract Background Direct-to-consumer (DTC) marketing of pharmaceuticals is controversial, yet effective. Little is known relating patterns of medication use to patient responsiveness to DTC. Methods We conducted a secondary analysis of data collected in national telephone survey on knowledge of and attitudes toward DTC advertisements. The survey of 1081 U.S. adults (response rate = 65%) was conducted by the Food and Drug Administration (FDA). Responsiveness to DTC was defined as an affirmative response to the item: "Has an advertisement for a prescription drug ever caused you to ask a doctor about a medical condition or illness of your own that you had not talked to a doctor about before?" Patients reported number of prescription and over-the-counter (OTC) medicines taken as well as demographic and personal health information. Results Of 771 respondents who met study criteria, 195 (25%) were responsive to DTC. Only 7% respondents taking no prescription were responsive, whereas 45% of respondents taking 5 or more prescription medications were responsive. This trend remained significant (p trend .0009) even when controlling for age, gender, race, educational attainment, income, self-reported health status, and whether respondents "liked" DTC advertising. There was no relationship between the number of OTC medications taken and the propensity to discuss health-related problems in response to DTC advertisements (p = .4). Conclusion There is a strong cross-sectional relationship between the number of prescription, but not OTC, drugs used and responsiveness to DTC advertising. Although this relationship could be explained by physician compliance with patient requests for medications, it is also plausible that DTC advertisements have a particular appeal to patients prone to taking multiple medications. Outpatients motivated to discuss medical conditions based on their exposure to DTC advertising may require a careful medication history to evaluate for therapeutic duplication or overmedication.